Individual and Collective Time-Consistency - Geir B. Asheim (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1995)
This paper reconsiders the Strotz-Pollak problem of consistent planning and argues that a solution to this problem requires a refinement of subgame-perfectness. Such a refinement is offered through an analysis based on Greenberg's 'theory of social situations'. A unifying framework is presented whereby consistent one-person planning as a problem of individual time-consistency and renegotiation-proofness as a problem of collective time-consistency are captured through the same general concept.
Keywords: 330